HIV/AIDS, Harm Reduction, and Neoliberal Containment Strategies in Contemporary UK Documentary Theatre - Louisa Hann (University of Edinburgh, 2021)
Using Peter Darney’s play 5 Guys Chillin’ as a case study, this essay explores how documentary theatre may operate as a distinctly neoliberal public health measure when it comes to reducing the risk of HIV transmission related to subcultural practices such as chemsex. The subject of countless sensationalist and tacitly homophobic headlines in recent years, chemsex has generated a kind of moral panic around gay subcultures in recent years, with several journalists and filmmakers erroneously condemning the practice as the main driver of HIV in the UK. Although Darney has described the play as an attempt to tackle such demonisation, 5GC inadvertently ends up restating pathologizing narratives surrounding chemsex via what Roger Foster has termed an ‘ethic of authenticity': the notion that one can reach happiness by adapting to normative ways of living and neoliberal health diktats. Combining Foster’s critique of neoliberal therapeutic culture and the fiction of “wellness” with Herbert Marcuse’s theories surrounding so-called ‘one-dimensional society’, this essay seeks to explain how 5GC paradoxically perpetrates its ethos of anti-prejudice by pathologizing interview subjects as victims of a subculture intent on rejecting its own societal oppression.